Implementation of Deep Learning in Project Based Learning on Early Childhood Independence - Made Vina Arie Paramita; Rendy Setyowahyudi; Ni Putu Vivin Indrawati; Rizky Drupadi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
Independence in early childhood is an important aspect of character development and life skills that need to be developed from an early age. However, in practice, children's independence has not yet been optimally developed. This study aims to analyze the level of implementation of deep learning in project-based learning in early childhood education and its relation to children’s independence. This study employed a qualitative approach. Data were collected through in-depth interviews with early childhood education teachers in Buleleng Regency, as well as observation questionnaires to assess children’s independence. There were six teachers interviewed and 20 children observed to strengthen the data. The results showed that children were able to demonstrate independent behavior across various indicators, namely learning initiative, responsibility, decision-making, discipline and time management, as well as perseverance during project activities. Several challenges in implementing Deep Learning in Project-Based Learning (PjBL) were identified, including differences in teachers’ understanding of the Deep Learning concept, limited instructional time, lack of contextual learning media and resources, uneven parental involvement, and the characteristics of early childhood learners who still require intensive guidance. Several contextual strategies were implemented, such as the use of projects based on daily activities, the provision of open-ended questions and simple reflections, the utilization of the surrounding environment as a learning resource, collaboration with parents, and the gradual application of scaffolding according to children’s developmental needs.